Determinants of carotid-femoral pulse wave velocity progression in hypertensive patients over a 3.7 years follow-up. (2nd January 2018) - Meani, Paolo; Maloberti, Alessandro; Sormani, Paola; Colombo, Giulia; Giupponi, Luca; Stucchi, Miriam; Varrenti, Marisa; Vallerio, Paola; Facchetti, Rita; Grassi, Guido; Mancia, Giuseppe; Giannattasio, Cristina
Abstract: Objective: The role of risk factors on the progression of arterial stiffness has not yet been extensively evaluated. The aim of the current longitudinal study was to evaluate the determinants of the PWV progression over a 4 years follow-up period in hypertensive subjects. Materials and Methods: We enrolled 333 consecutive hypertensive outpatients 18–80 aged, followed by the Hypertension Unit of St. Gerardo Hospital (Monza, Italy). At baseline anamnestic, clinical, BP, laboratory data and cfPWV were assessed. We performed a PWV follow-up examination with a median time amounting to 3.75 ± 0.53 years. Results: At baseline the mean age was 54.5 ± 12.6 years, SBP and DBP were 141.3 ± 18.6 and 86.4 ± 10.4 mmHg and PWV was 8.56 ± 1.92 m/s. Despite an improvement in BP control (from 37 to 60%), at follow-up the population showed a PWV increase (ΔPWV 0.87 ± 3.05 m/s). PWV and ΔPWV gradually increased in age decades. In patients with uncontrolled BP values at follow-up ΔPWV showed a greater increase as compared to patients with controlled BP (1.46 ± 3.67 vs 0.62 ± 2.61 m/s, p  < .05). The independent predictors of ΔPWV were age, baseline PWV, baseline SBP/MBP and ΔSBP/MBP. Conclusions: the accelerated arterial aging in treated hypertensive subjects is in large measure explained by age and BP values. PWV changes over time would probably give important information that need further future research studies.